Investigating the Correlation between Prescriptive Grammar Knowledge and Speaking Ability in EFL Students - Shafira, Zahrani Bunga; Novitri, Novitri; Safriyanti, Maria (Lectura : Jurnal Pendidikan, 2025)
Prescriptive grammar knowledge refers to established rules and guidelines that define the proper and standardized use of English. In English as a Foreign Language (EFL) context, grammar mastery significantly shapes students’ speaking ability. However, an overemphasis on grammatical accuracy may affect learners’ confidence due to anxiety and social pressure, especially in academic settings. Speaking becomes one of the most challenging skills when students feel pressured to speak correctly. The purpose of this study was to investigate whether there is a significant correlation between students’ perception of prescriptive English grammar and their speaking ability. The sample were 38 fourth-semester English Department students at Universitas Riau, selected through cluster random sampling. Data were collected through a questionnaire that measured students’ perception of prescriptive grammar and a speaking test assessed by three independent raters. All of the data in this study were analyzed and confirmed using SPSS 30.0. Validity testing showed all questionnaire items exceeded the critical value (0.3202), indicating validity. The reliability coefficient was 0.777, surpassing the 0.6 threshold. Inter-rater reliability coefficient was confirmed with a significance value of 0.000. Pearson Product Moment Correlation analysis was conducted in this research. The results showed a strong positive correlation between students’ perceptions and their speaking performance (r = 0.957, p = 0.000). These findings support the alternative hypothesis (Ha) and reject the null hypothesis (H0). This study informs how learners’ views about grammar may influence their speaking ability and offers practical ideas for improving EFL teaching, especially in the Indonesian context.